Research on Optimal Method of Multi-regional Power Grid Investment Project. Issue 5 (January 2021) - Li, Hui; Liu, Zifa; Yu, Puyang; Wang, Zhidong; Zhao, Lang
Abstract: The optimization of multi-regional power grid investment projects is the basis for ensuring the benefits of power companies and can meet the urgent needs of power grid development. This article first takes the historical benefits of power grids, planning benefits, power grid scale and development needs as indicators to establish a multi-regional power grid investment project optimization index system. Then this article puts forward the investment project optimization model. With the goal of maximizing investment benefits, with project portfolio constraints, grid scale development demand constraints and investment constraints as constraints, the binary particle swarm algorithm is used to optimize the investment project portfolio schemes of various regions. Finally, an example is used to verify the effectiveness and feasibility of the method proposed in this paper.